Venezuelan Amazon in chaos: economic and social crisis - Osorio Bohórquez, Leonardo Favio (Cuadernos Latinoamericanos, 2020)
The Amazonas state located in the Bolivarian Republic of Venezuela is in the spotlight as a result of its natural wealth. In recent years, the economic situation that the country is going through has had a strong impact on the region, whose deficit in food and public services such as gas, transportation or fuels, is perhaps more intense than in other regions. In this scenario, the objective of this work was to analyze how the economic and social situation in Amazonas has worsened. Two fundamental problems are studied: the economic crisis and the guerrilla presence together with the mining problem. Through the use of the historical method, the use of oral history and the use of qualitative methodology, with the application of unstructured open interviews, the contribution of some indigenous and Creole testimonies was taken in order to know their vision about of this problem in the region. It is concluded that both indigenous and creole groups are affected by the current situation due to the increase in hyperinflation and the generalized shortage of goods and services, together with the increase in violence from disputes over the control of mines.